Strategi Humas Kejaksaan Agung dalam Mengelola Reputasi Institusi di Mata Publik - Reza Ramadhan; Bonardo Marulitua A; M. Ismail Alif (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to conduct an in-depth exploration of the public relations communication strategy of Kejaksaan Agung in maintaining and strengthening its institutional reputation amidst the dynamics of media coverage, increasing public demands for transparency, and the persistently low level of legal literacy in society. This research employs a qualitative method with a descriptive approach grounded in the constructivist paradigm. Data were collected through document analysis, direct observation of public relations activities, and in-depth interviews with key informants. The data analysis is based on the strategic public relations framework developed by Ronald D. Smith (2021), which comprises four essential phases: formative research, strategy formulation, tactical implementation, and evaluation. The findings indicate that Humas Kejaksaan Agung implements an adaptive and participatory communication approach through the integration of intelligence-based digital analytics, data-driven institutional issue mapping, the development of law-focused educational content, and a rapid response mechanism to public issue dynamics. These findings highlight a strategic innovation that has not been widely discussed in existing public relations literature, particularly within the context of law enforcement institutions. Furthermore, this approach reflects a paradigm transformation from bureaucratic communication models to collaborative, evidence-based, and digitally responsive strategies aligned with public opinion dynamics. Practically, the study recommends strengthening human resource capacity in public relations, particularly in strategic communication competence and legal literacy, to ensure sustained and consistent reputation management in the digital era. Academically, this research provides a conceptual contribution to the development of a strategic communication model for public institutions grounded in formative research and real-time media analytics.